2021
DOI: 10.1609/icwsm.v10i1.14819
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting the Mind and Instagramming the Heart: Exploring Differentiated Content Sharing on Social Media

Abstract: Understanding the usage of multiple Online Social Networks (OSNs) is of significant research interest as it helps in identifying the distinguishing traits of each social media platform that contribute to its continued existence. A comparison between two OSNs is particularly useful when it is done on the representative set of users holding active accounts on both the platforms. In this research, we collected a set of users holding accounts on both Twitter and Instagram. An extensive textual and visual analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Therefore, this research created a system that can determine the topic of a caption on Instagram. Manikonda et al [2016] was one of the critical studies exploring Instagram and Twitter users, concerning user activities and demographics. Identifying a topic of discussion of social media is not an easy task, as the text were available in large volume Arora et al [2018], unstructured and informal Kang and Lee [2017].…”
Section: Author 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this research created a system that can determine the topic of a caption on Instagram. Manikonda et al [2016] was one of the critical studies exploring Instagram and Twitter users, concerning user activities and demographics. Identifying a topic of discussion of social media is not an easy task, as the text were available in large volume Arora et al [2018], unstructured and informal Kang and Lee [2017].…”
Section: Author 1 Introductionmentioning
confidence: 99%
“…Some previous studies have successfully used LDA to create a topic model. Manikonda et al [2016] has revealed topic modelling in Instagram and Twitter. Liu and Jansson [2017] exploits LDA to create a topic model of an Instagram caption in English that reveals some topics as well as sentiments analysis.…”
Section: Author 1 Introductionmentioning
confidence: 99%
“…Related work has focused on differences in sentiment analysis of content generated across platforms. For instance, while examining the posts posted by the same group of users on Instagram and Twitter, (Manikonda, Meduri, and Kambhampati 2016) saw that posts on Twitter contain more negative expressions than posts on Instagram. (Ali et al 2023) also argued that meta-data features (e.g., conversation length) were better predictors of risky conversations on Instagram.…”
Section: Related Workmentioning
confidence: 99%
“…Although many works have been studying linguistic differences on multiple platforms, no work has explored the linguistic differences for harmful content posted by communities across multiple platforms, which is a gap our work fills. Moreover, existing tools for cross-platform comparison are limited to sentiment analysis and conventional topic modeling next to temporal frequency counts (e.g., the number of comments with negative sentiment (Manikonda, Meduri, and Kambhampati 2016;Lin and Qiu 2013;Ruan et al 2022), or the number of links to deleted YouTube videos (Yang et al 2021)). Our study goes beyond sentiment analysis and makes nuanced comparisons across several axes.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, platforms such as Instagram also generate a lot of content centred around social activities (de Juan et al, 2021). Activity on Twitter's platform is primary focused around topical discourse (Manikonda et al, 2021). These framings have an effect on the type of preferences expressed through different sources of crowdsourced data because users work towards the social norms established within the online space (Calcagni et al, 2019;Venturelli et al, 2017).…”
Section: Purposementioning
confidence: 99%